2007
DOI: 10.1016/j.brainres.2006.10.056
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of transcriptional modulation of the presenilin 1 gene promoter by ZNF237, a candidate binding partner of the Ets transcription factor ERM

Abstract: DNA sequences required for the expression of the human presenilin 1 (PS1) gene have been identified between -118 and +178 flanking the major initiation site (+1) mapped in SK-N-SH cells. Several Ets sites are located both upstream as well as downstream from the +1 site, including an Ets motif present at -10 that controls 90% of transcription in SK-N-SH cells. However in SH-SY5Y cells transcription initiates further downstream and requires an alternative set of promoter elements including a +90 Ets motif. Ets2,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 36 publications
0
17
0
Order By: Relevance
“…We have previously shown that ZNF237 and CHD3 repress PS1 transcription and PS1 protein level in human neuroblastoma cells (Lee and Das 2010; Pastorcic and Das 2007a,b). To determine the role of ZNF237 and CHD3 in controlling the function of ER Ca 2+ leak channels, we performed Ca 2+ ‐imaging experiments in the presence of extracellular Ca 2+ in SK‐N‐SH cells which were transiently transfected with pCMV‐Tag2 or pCMV‐Tag2‐ZNF237 or pCMV‐Tag2‐CHD3 constructs for 48 h. Cell extracts were prepared and levels of FLAG‐ZNF237 and FLAG‐CHD3 were determined using western blot analysis using anti‐FLAG antibody, and PS1 level was determined by anti‐PS1 antibody as described before (Pastorcic and Das 2007b; Lee and Das 2010).…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…We have previously shown that ZNF237 and CHD3 repress PS1 transcription and PS1 protein level in human neuroblastoma cells (Lee and Das 2010; Pastorcic and Das 2007a,b). To determine the role of ZNF237 and CHD3 in controlling the function of ER Ca 2+ leak channels, we performed Ca 2+ ‐imaging experiments in the presence of extracellular Ca 2+ in SK‐N‐SH cells which were transiently transfected with pCMV‐Tag2 or pCMV‐Tag2‐ZNF237 or pCMV‐Tag2‐CHD3 constructs for 48 h. Cell extracts were prepared and levels of FLAG‐ZNF237 and FLAG‐CHD3 were determined using western blot analysis using anti‐FLAG antibody, and PS1 level was determined by anti‐PS1 antibody as described before (Pastorcic and Das 2007b; Lee and Das 2010).…”
Section: Resultsmentioning
confidence: 97%
“…Wild type PS1 cDNA was cloned into pCDNA3 vector to produce pCDNA3.PS1. Constructions of pCMV.p53, pCMV‐Tag2‐ZNF237, pCMV‐Tag2‐CHD3 were reported previously (Pastorcic and Das 2000, 2007b,a). SK‐N‐SH cells were seeded in culture dishes on to glass coverslips the day before transfection.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Functionally, PSPC1 was proposed to participate in the regulation of transcription (Passon et al 2011). ZMYM5 belongs to the zinc finger MYM-type family and probably has molecular functions, such as metal ion binding or zinc ion binding (Pastorcic and Das 2007). Although the phenotype–genotype correlation remains unclear and one smaller deletion within this region was reported in the control group (DGV; nsv455826) (Itsara et al 2009), we propose that the identified de novo 13q12.11 deletion could contribute to the clinical features observed in our patient.
Fig.
…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we have studied the regulation of transcription of the human PS1 gene. We have shown that Ets1/2 transcription factors upregulate PS1 transcription (14)(15)(16)(17), whereas transcription factors p53, ZNF237, and CHD3 downregulate PS1 transcription (15,18,19). We have recently shown that inhibition of basal JNK activity by JNK inhibitor SP600125 represses PS1 transcription by a p53 dependent mechanism and also reduces PS1 protein level (1).…”
Section: Introductionmentioning
confidence: 99%